A case of capecitabine-induced dermatomyositis - Saraswat, Neerja (Indian J Pharmacol, 2018)
Dermatomyositis (DM) is an idiopathic, inflammatory connective tissue disorder characterized by symmetrical proximal myopathy and characteristic skin involvement. The pathogenesis of DM is widely debated; however, it is postulated to be an end result of immune-mediated cascade, triggered by multiple environmental factors in a genetically predisposed individual. In addition to underlying malignancies, many drugs have been reported to be associated with DM. Capecitabine is a chemotherapeutic agent, approved by the United States-Food and Drug Administration for the management of colonic, metastatic colonic, and metastatic breast carcinoma. It is converted into 5-fluorouracil after oral intake. Common dose-limiting toxicities associated with the usage of the capecitabine include increased bilirubin levels, diarrhea, and hand-foot syndrome. DM-induced by capecitabine has rarely been reported. Herein, we describe a patient of metastatic carcinoma breast, who developed DM after capecitabine intake. The patient had accidental re-challenge with capecitabine resulting in the reappearance of the cutaneous and musculoskeletal system, thereby confirming our diagnosis of drug-induced DM in the setting of underlying malignancy.